1994
DOI: 10.1021/jo00094a044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Chiral Dendrimer Derived from Pentaerythritol

Abstract: The synthesis and characterization of chiral dendrimer 1 in its racemic form is reported. The chirality of this macromolecule, with a molecular weight of 2831, is based on a pentaerythritol core, acting as a stereocenter with four dendritic substituents of different generation. The synthesis is making use of a newly developed, general route to a multisubstituted pentaerythritol derivative.Resolution of 1 is hampered by conformational flexibility. The latter, however, allows detailed 'H-NMR characterization ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This core was considered as a potential source for the fabrication of non-symmetrical segmented dendrimers (Fig. 2, structures C and D) by regio-selective chemistry leading to a ''selective multifunctionalization'' of the pentaerythritol unit [16,19]. However, the synthesis of the symmetrical dendrimer was already found to be rather difficult itself, and this approach was later abandoned as totally inapplicable for the synthesis of Janus-like dendrimers.…”
Section: Octopus Lcsmentioning
confidence: 99%
“…This core was considered as a potential source for the fabrication of non-symmetrical segmented dendrimers (Fig. 2, structures C and D) by regio-selective chemistry leading to a ''selective multifunctionalization'' of the pentaerythritol unit [16,19]. However, the synthesis of the symmetrical dendrimer was already found to be rather difficult itself, and this approach was later abandoned as totally inapplicable for the synthesis of Janus-like dendrimers.…”
Section: Octopus Lcsmentioning
confidence: 99%
“…(3) chiral substructures within a c~al dendrimer should be detectable by optical measurements. Figure 3- The first report of purely organic chiral dendrimers was published by Newkome et al 103 They prepared a four-directional core molecule from pentaerythritol that has been elongated with tris[ carboxyethoxymethyl] amino-methane branching units using standard…”
Section: Detectionmentioning
confidence: 99%
“…The compound was prepared as described in a method by Kremers and Meijer for the treatment of hydroxymethylmalonates with MEM chloride. 25 A solution of MEM chloride (26.2 g, 210 mmol), 4-hydroxybenzonitrile (22.5 g, 190 mmol) and diisopropylethylamine (39 cm 3 ) in dry CH 2 Cl 2 (275 cm 3 ) was stirred at room temperature until TLC analysis (with hexane-ethyl acetate, 2 : 1) indicated that conversion was complete. The reaction mixture was then washed with saturated aqueous NaHCO 3 (3 × 150 cm 3 ), dried over MgSO 4 , filtered, and concentrated in vacuo.…”
Section: -(2-methoxyethoxymethoxymentioning
confidence: 99%